2021
DOI: 10.1002/2211-5463.13165
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 mediates bone marrow mesenchymal stem cell adipogenesis to promote chemoresistance in acute myeloid leukaemia

Abstract: Adipogenesis of bone marrow mesenchymal stem cells (MSCs) promotes chemoresistance of acute myeloid leukaemia (AML) cells. MSCs from AML patients (AML‐MSCs) display enhanced adipogenesis compared with bone marrow MSCs from healthy donors. However, the precise molecular mechanism by which adipogenesis of MSCs from AML marrow differs from normal counterparts remains obscure. We found that METTL3 significantly inhibits MSC adipogenesis. Here, we aimed to identify the molecular mechanism linking METTL3 and MSC adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…also reported that METTL3 was more highly expressed in immature cells than in mature monocytes, and its depletion significantly inhibited cell proliferation and decreased MYC expression and m 6 A levels on MYC mRNA ( 66 ). Recently, a group of researchers reported that METTL3 plays a role in inhibiting adipogenesis of bone marrow mesenchymal stem cells (MSCs) and blocking the chemoresistance of acute myeloid leukemia cells by regulating the PI3K/AKT signaling pathway ( 58 ). However, METTL3 expression was significantly decreased in AML-MSCs, which enhanced the adipogenesis and chemoresistance of AML cells ( 58 ).…”
Section: The Biological Function Of Mettl3mentioning
confidence: 99%
See 2 more Smart Citations
“…also reported that METTL3 was more highly expressed in immature cells than in mature monocytes, and its depletion significantly inhibited cell proliferation and decreased MYC expression and m 6 A levels on MYC mRNA ( 66 ). Recently, a group of researchers reported that METTL3 plays a role in inhibiting adipogenesis of bone marrow mesenchymal stem cells (MSCs) and blocking the chemoresistance of acute myeloid leukemia cells by regulating the PI3K/AKT signaling pathway ( 58 ). However, METTL3 expression was significantly decreased in AML-MSCs, which enhanced the adipogenesis and chemoresistance of AML cells ( 58 ).…”
Section: The Biological Function Of Mettl3mentioning
confidence: 99%
“…Recently, a group of researchers reported that METTL3 plays a role in inhibiting adipogenesis of bone marrow mesenchymal stem cells (MSCs) and blocking the chemoresistance of acute myeloid leukemia cells by regulating the PI3K/AKT signaling pathway ( 58 ). However, METTL3 expression was significantly decreased in AML-MSCs, which enhanced the adipogenesis and chemoresistance of AML cells ( 58 ). They found that METTL3 impacted the m 6 A modification of AKT1 mRNA, resulting in a decrease in the protein level of AKT1 and an increase in adipogenesis.…”
Section: The Biological Function Of Mettl3mentioning
confidence: 99%
See 1 more Smart Citation
“…in AML cells, thus further suggesting that METTL3 can act as an oncogenic factor in myeloid malignancies, which is an important reference value for clinical treatment. Similarly, the molecular mechanism between METTL3 and adipogenesis in mesenchymal stem cells of AML patients (AML-MSCs) has been currently identified [ 147 ]. Based on the analysis of m 6 A epigenetic changes in MSCs identified by RIP-qPCR and MeRIP-qPCR, deletion of METTL3 in AML-MSCs can facilitate increased production of AKT protein through controlling m 6 A modifications of AKT1-mRNA, leading to excessive MSC adipogenesis and consequently making AML cells resistant to chemotherapy.…”
Section: M 6 a Methylation Modifications And Hematological Malignanciesmentioning
confidence: 99%
“…In the process of adipogenic differentiation, METTL3 expression negatively regulated adipogenic differentiation of porcine BMSCs via the JAK1/STAT5/C/EBPβ pathway in an m 6 A-YTHDF2-dependent manner ( Yao et al, 2019 ). Moreover, METTL3 inhibited expression of AKT protein in BMSCs by mediating m 6 A RNA methylation of AKT1, thus reducing MSC adipogenesis and alleviating chemoresistance in AML cells ( Pan et al, 2021 ). METTL14 was also involved in the proliferation and osteogenic differentiation of BMSCs, which triggered the m 6 A RNA methylation of PTPN6 to increase its mRNA stability and activated Wnt signaling pathway to enhance cell proliferation and osteogenic differentiation ( Cheng et al, 2021 ).…”
Section: The Role Of M 6 a In Ascsmentioning
confidence: 99%